Terapi Komplementer dengan Indikator Eastern Cooperative Oncology Group Performance Scale (ECOG-PS) pada Pasien Kanker dengan Kemoterapi - Dzakiyatul Fahmi Mumtaz; Chlara Yunita Prabawati; Ito Wardin; Gangga Kristin Nurfiyatul Jannah; Shaleza Mellaty Putri (FORIKES, 2024)
Chemotherapy is a common therapy in cancer treatment with many side effects of treatment and psychological stress. One indicator to assess the performance scale of cancer patients with chemotherapy is the Eastern Cooperative Oncology Group Performance Scale (ECOG-PS). Various complementary therapy options with ECOG-PS indicators can be chosen by cancer patients to maintain quality of life and chemotherapy symptom management. This study aimed to determine collaborative nursing therapies with ECOG-PS indicators to maintain quality of life and reduce symptoms due to chemotherapy. This study was a literature review, based on research results published from October 2018 to April 2023, which were limited to complementary therapies with ECOG-PS indicators in cancer patients with chemotherapy. The literature was obtained from 3 databases, namely PubMed, Sage and ScienceDirect. Two researchers independently extracted and evaluated studies that met the inclusion and exclusion criteria. Analysis of the results before and after therapy was carried out descriptively narratively related to the effectiveness of therapy in cancer patients with chemotherapy, which were divided into exercise and non-exercise therapy. From the review results, 8 selected experimental studies were obtained which were conducted on 393 cancer patients undergoing chemotherapy (mean age of patients 49-75 years). The ECOG-PS indicator score 0-1 was used as an indicator in the inclusion criteria for respondents in 6 selected studies (60%). Recommended exercise therapies include exercise & nutritional intervention, home-based exercise prehabilitation, The ABCSG C07 exercise, and multicomponent exercise program. Recommended non-exercise therapies: early palliative care intervention, herbal therapy & CBT, and progressive relaxation exercise. Furthermore, it was concluded that there are 2 types of complementary therapies, namely exercise and non-exercise therapy, which can be selected to maintain the quality of life and symptom management of chemotherapy patients.Keywords: cancer patients; chemotherapy; Eastern Cooperative Oncology Group Performance Scale; performance scale ABSTRAK Kemoterapi adalah terapi yang sering dilakukan dalam pengobatan kanker dengan banyak efek samping pengobatan dan stress psikologis. Salah satu indikator untuk menilai skala kinerja pasien kanker dengan kemoterapi adalah Eastern Cooperative Oncology Group Performance Scale (ECOG-PS). Berbagai pilihan terapi komplementer dengan indikator ECOG-PS dapat dipilih oleh pasien kanker untuk mempertahankan kualitas hidup dan manajemen gejala kemoterapi. Studi ini bertujuan untuk mengetahui terapi-terapi kolaboratif keperawatan dengan indikator ECOG-PS untuk mempertahankan kualitas hidup dan mengurangi gejala akibat kemoterapi. Studi ini merupakan tinjauan literatur, dengan bersumber pada hasil-hasil penelitian yang diterbitkan mulai Oktober 2018 hingga April 2023, yang dibatasi pada terapi komplementer dengan indikator ECOG-PS pada pasien kanker dengan kemoterapi. Literatur didapatkan dari 3 database yaitu PubMed, Sage dan ScienceDirect. Dua peneliti secara independen mengestraksi dan mengevaluasi studi yang memenuhi kriteria inklusi dan eksklusi. Analisis hasil sebelum dan sesudah terapi dilakukan secara deskriptif naratif terkait efektifitas terapi pada pasien kanker dengan kemoterapi, yang terbagi menjadi terapi latihan dan non latihan. Dari hasil tinjauan didapatkan 8 penelitian eksperimental terpilih yang dilakukan pada 393 pasien kanker yang menjalani kemoterapi (usia rata-rata pasien 49-75 tahun). Indikator ECOG-PS skor 0-1 dijadikan sebagai indikator dalam kriteria inklusi responden pada 6 penelitian terpilih (60%). Terapi latihan yang direomendasikan di antaranya adalah exercise & nutritional intervention, home based exercise prehabilitation, The ABCSG C07 exercise, dan multicomponent exercise program. Terapi non Latihan yang direkomendasikan: early palliative care intervention, herbal therapy & CBT, serta progressive relaxation exercise. Selanjutnya disimpulkan bahwa terdapat 2 jenis terapi komplementer yakni terapi latihan dan non latihan yang dapat dipilih untuk mempertahankan kualitas hidup dan manajemen gejala pasien kemoterapi.Kata kunci: pasien kanker; kemoterapi; Eastern Cooperative Oncology Group Performance Scale; skala kinerja